Gasless single-port laparoscopic-assisted vaginal hysterectomy for large uteri weighing 500 g or more. (August 2016) - Takeda, Akihiro; Hayashi, Shotaro; Imoto, Sanae; Nakamura, Hiromi
Abstract: Objective: To evaluate the safety and feasibility of gasless transumbilical single-port laparoscopic-assisted vaginal hysterectomy (LAVH) for the management of large uteri weighing 500 g or more. Study design: We conducted a retrospective comparative study of women with large uteri, each undergoing gasless multi-port or single-port LAVH. Preoperatively, gonadotropin-releasing hormone agonist was administered and autologous blood was donated except for cases requiring immediate surgery. Additionally, intraoperative blood salvage and donation was performed in select cases. In single-port LAVH, a wound retractor was used to make a working port through umbilical incision. After the surgical view was secured using an abdominal wall-lift device, the surgical procedures were performed using conventional laparoscopic instruments. In select cases, temporary endovascular occlusion of the bilateral internal iliac arteries was performed to reduce intraoperative hemorrhaging. Results: Of the 650 women managed by multi-port or single-port LAVH, 55 and 67 women each with uteri weighing 500 g or more, respectively, were included. In single-port LAVH group, the median age was 47 years. Twelve women were nulliparous and 3 women with 2 cesarean deliveries each, had never had a vaginal delivery. The most frequent surgical indication was uterine myoma. In the single-port LAVH group, the surgical procedures included LAVH alone ( n  = 36), LAVH and bilateral salpingo-oophorectomy ( n  = 22), LAVH and unilateral salpingo-oophorectomy ( n  = 8), and LAVH and appendectomy ( n  = 1). Extensive adhesiolysis was required in eight cases. The median extirpated tissue weight was 652 g with a median estimated intraoperative blood loss of 450 mL. A significant positive linear correlation was observed between the operative time or estimated blood loss and the extirpated uterine weigh. Although excessive bleeding exceeding 1000 mL was noted in 15 cases, a transfusion of bank blood was not required by using preoperatively donated autologous blood and intraoperative autologous blood salvage and donation. Extended hospitalization was required in six cases. The median surgical duration in the single-port LAVH group was significantly longer than that in the multi-port LAVH group. Conclusion: Gasless single-port LAVH is a feasible alternative that can yield similar major surgical outcomes as multi-port LAVH, with potential cosmetic benefit.